'I wanted to be a bus conductor for the free travel' - Ching Abdullah, Yaqin (2012)
AT a talk, TV host and motivational writer and speaker Datuk Mohd Fadzilah Kamsah, 60, tells the audience: "Don't be an exemplary individual for your company".